2017
DOI: 10.1093/jac/dkx397
|View full text |Cite
|
Sign up to set email alerts
|

Molecular relatedness of ESBL/AmpC-producing Escherichia coli from humans, animals, food and the environment: a pooled analysis

Abstract: Our 'One Health' approach provides an integrated evaluation of the molecular relatedness of ESBL/AmpC-EC from numerous sources. The analysis showed distinguishable ESBL/AmpC-EC transmission cycles in different hosts and failed to demonstrate a close epidemiological linkage of ESBL/AmpC genes and plasmid replicon types between livestock farms and people in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
123
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(151 citation statements)
references
References 56 publications
15
123
4
1
Order By: Relevance
“…There appears to be limited overlap between extended‐spectrum cephalosporinase E. coli recovered from animals (or derived foods) and the general human population (Börjesson et al., ; Day et al., ; Nguyen et al., ; Wu et al., ). However, human–animal sharing of closely related strains or plasmid types has been observed, especially in farmers (Dorado‐García et al., ; van Hoek, Stalenhoef, van Duijkeren, & Franz, ), and consequently there is a particular focus around the licensing and use of these antibiotic classes in agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…There appears to be limited overlap between extended‐spectrum cephalosporinase E. coli recovered from animals (or derived foods) and the general human population (Börjesson et al., ; Day et al., ; Nguyen et al., ; Wu et al., ). However, human–animal sharing of closely related strains or plasmid types has been observed, especially in farmers (Dorado‐García et al., ; van Hoek, Stalenhoef, van Duijkeren, & Franz, ), and consequently there is a particular focus around the licensing and use of these antibiotic classes in agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…E. coli are the most reported ESBL/AmpC-producing enterobacteria worldwide, with increasing frequency from animals, food, environmental sources and humans. In recent years, CR- E. coli transmission has been reported in different hosts, demonstrating a close human-animal ESBL/AmpC gene similarity between livestock (broilers and pigs) and personnel working at the farms [10]. Additionally, similar CR genes have been reported between isolates from the community and those from human clinical settings, sewage water and wild birds [10].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, CR- E. coli transmission has been reported in different hosts, demonstrating a close human-animal ESBL/AmpC gene similarity between livestock (broilers and pigs) and personnel working at the farms [10]. Additionally, similar CR genes have been reported between isolates from the community and those from human clinical settings, sewage water and wild birds [10]. Although ESBL transmission has been studied extensively in Enterobacteriaceae from humans and livestock, data on antimicrobial resistance in the environment is still limited [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Tanzania, for example, genotypic similarity has been documented between resistant enteric bacteria in people, animals (both livestock and wildlife) and the environment (i.e., waters sources) [8,9] Similar patterns were found in Salmonella isolates from people and animals in Uganda [10]. In contrast, genotypic studies from high-income countries have largely shown distinguishable epidemics of AMR in livestock and the general population [1113]. These patterns within HICs are consistent with limited contact between the general population and livestock and with the more developed health, sanitation, and regulatory infrastructures that limit transmission events [1115].…”
Section: Introductionmentioning
confidence: 99%